(3efThQ CHj Ydis - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hUd cJGHc jG CNj GdYRjR Ydi hYfOi CWGd Gddg HbGc hCOGe YRc hfYeGc hhbaJ Ydjg hTcQJ ef dGjNjH TcQg s
(3BNQgG (B:s
(3adjHdZ Pdc hjaQb eG jMUd efg Ydi GdVYaGA ef GdCgd hGdHfGJ hCeG GdSja JeJ Hefg hdi GdCeQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B98s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds